2014
DOI: 10.1055/s-0034-1371021
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal Applications of PET/MR

Abstract: To overcome each limitation of morphological and functional imaging procedures, hybrid imaging systems have been developed and introduced into clinical routine. It has been increasingly discussed whether magnetic resonance imaging (MRI) might be an appropriate alternative for computed tomography (CT). The major advantage of positron emission tomography (PET)/MR consists of combined metabolic and anatomical information in a single imaging session that provides superior soft tissue characterization of MRI over C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 70 publications
0
8
0
1
Order By: Relevance
“…Ayrıca özellikle yumuşak doku sarkomlarında tedaviye yanıtın değerlendirilmesi için FDG PET/ MR görüntülemeden yararlanılabilir (29). Sklerotik kemik lezyonları BT ile daha kolay saptanabilirken, özellikle osteopenik hastalarda ve kortikal kemiğin etkilenmediği durumlarda litik kemik lezyonları BT'de fark edilemeyebilir.…”
Section: Kas-i̇skeletsistemiunclassified
“…Ayrıca özellikle yumuşak doku sarkomlarında tedaviye yanıtın değerlendirilmesi için FDG PET/ MR görüntülemeden yararlanılabilir (29). Sklerotik kemik lezyonları BT ile daha kolay saptanabilirken, özellikle osteopenik hastalarda ve kortikal kemiğin etkilenmediği durumlarda litik kemik lezyonları BT'de fark edilemeyebilir.…”
Section: Kas-i̇skeletsistemiunclassified
“…Another usefulness clinical application is therapeutic response assessment, especially in soft tissue sarcomas. 80 For malignant bone lesions, it is expected that PET/MRI is more robust and would provide a better anatomical delineation when compared with PET/CT. However, for this, additional dedicated sequences rather than only two basic sequences might be needed.…”
Section: Musculoskeletalmentioning
confidence: 99%
“…Despite the known FDG avidity for inflammatory activity, there are no data to support PET/MRI as a possible imaging method, for example, in arthropathies (psoriasis, rheumatoid arthritis, gout, and ankylosing spondylitis). 80 …”
Section: Musculoskeletalmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Time-of-flight (TOF) measurement capability is an important feature of modern whole-body PET systems because the reconstruction of PET images using a TOF kernel results in a significant improvement in image quality. [6][7][8] Recent studies also have shown that the TOF information leads to improved accuracy in the joint estimation of the radioactivity distribution and attenuation coefficient map. 9,10 Also, a high spatial resolution is required in PET scanners, which are designed for scanning specific human organs, such as the brain and breast, and small animals.…”
Section: Introductionmentioning
confidence: 99%